14%-efficiency fullerene-free ternary solar cell enabled by designing a short side-chain substituted small-molecule acceptor. (October 2019) - Chang, Yuan; Zhang, Xin; Tang, Yabing; Gupta, Monika; Su, Dan; Liang, Jiaen; Yan, Dong; Li, Kun; Guo, Xuefeng; Ma, Wei; Yan, He; Zhan, Chuanlang
Abstract: A new fused-ring electron acceptor (FREA) IEICF-DMOT was designed and synthesized with 3, 4-dimethoxylthiophene (DMOT) as the π−bridges to link the IDT core and the end IC-2F units. Compared to IEICO-4F which uses 3-(2-ethylhexyloxyl)thiophene as the bridge, IEICF-DMOT with two much shorter side chains (methoxyl) on the π−bridge exhibits a higher level of the lowest unoccupied molecular orbital (LUMO) (−3.85 vs. −3.93 eV), broadening absorption band, larger absorptivity, and a larger bandgap (1.38 vs. 1.27 eV), but reduced crystallinity in both the in-plane (100) and out-of-plane (010) directions, which makes a 0.13 V-larger open-circuit voltage ( V oc ) with a 10%-higher external quantum efficiency (EQE) and 9%-higher fill factor (FF), and thereby, a power conversion efficiency (PCE) of 13% in comparison with the IEICO-4F 10% efficiency. Adding the crystalline and narrower bandgap IEICO-4F as the near infrared absorber, the PBDB-T:IEICF-DMOT:IEICO-4F (1:1:0.1) ternary blend shows increased crystallinity for both donor and acceptor phases with increased hole and electron mobilities, achieving increased short-circuit current-density ( J sc ) and FF, and therefore, a promising PCE of 14%. These results indicate that DMOT with short side-chains on the thiophene-3, 4-positions is a promise bridge unit to design nonfullerene small-molecule acceptors with tunable energy levels, optical bandgap, and crystallinity to simultaneously increase V oc, EQE, and FF, and ultimately, efficiency. Graphical abstract: Image 1 Highlights: 3, 4-dimethoxylthiophene (DMOT), a new π-bridge for designing nonfullerene acceptor with improved absorption property. A new fused-ring electron acceptor, IEICF-DMOT reported. The use of DMOT enables LUMO level upshifted and absorption broadened, helpful for obtaining increased V oc and J sc . The use of short methoxyl side chains on the π−thiophene enables to reduce the crystallinity. 13% and 14% efficiencies fullerene-free binary and ternary solar cells obtained.